Prof Amar Singh Sirohi - AERA (Agricultural Economics Research Review, 2023)
The Agricultural Economics Research Association (India) deeply mourns the demise of its founder President, Professor Amar Singh Sirohi, on 19th January, 2018 at the age of 92. After his initial education in India, he obtained his doctoral degree in agricultural economics from Kansas State University (USA). On returning from USA, he served the Planning Commission, Government of India for a brief stint. In 1964, he joined the Indian Agricultural Research Institute, New Delhi as senior faculty, and soon became Professor and later as Head of the Division of Agricultural Economics in 1974, a position he served till his superannuation in 1986.